Analysis of public service quality at the Teluk Ambon district office in Ambon city - Aminah Bahasoan (Institute of Computer Science (IOCS), 2023)
This research aims to analyze and clarify the public service delivery mechanism, influencing factors on service quality, strategies to enhance public service quality, and optimize public service quality at the Teluk Ambon District Office in Ambon City. The study employs phenomenology and a qualitative descriptive approach. Data collection includes interviews, questionnaires, and documentation, with data analysis using triangulation and quantitative methods. Results show that the community generally perceives sub-district office services as satisfactory, with a Community Satisfaction Index (CSI) of 3.15. However, the assessment reveals (1) adherence to standard operating procedures (SOP) set by the Ambon city government, supported by an ISP assessment of priority III. (2) Factors affecting public services, such as professionalism and leadership. The Teluk Ambon Sub-district office's efficiency is hindered by centralized authority, preventing crucial decisions by the Camat. (3) Strategies for improving service quality face challenges due to this centralized authority. Nonetheless, officials at various levels display reliability, responsiveness, and empathy. Priorities for improvement include delegating authority and discretion, as indicated by ISP rankings.